Predicting ion diffusion in fly ash cement paste through particle analysis. (22nd February 2021) - Kang, Shinhyu; Tyler Ley, M.; Behravan, Amir
Highlights: The Particle Model can be used to predict apparent iodide diffusion coefficient in fly ash concrete. All the R-squared values of predictive models are >0.90 for 20% and 40% fly ash replacement levels. Different group has different impacts on the apparent iodide diffusion coefficient at a specific time period. The impacts of each group can be affected by the replacement level of fly ash. Abstract: Mass transport in concrete is an important factor to control the durability of concrete structures. Fly ash is commonly used as an additive to help reduce the mass transport of concrete. Since fly ash is a waste product, it is challenging to predict the performance of fly ash in concrete. This work uses a technique called the Particle Model to predict the reactivity and modification of the diffusion coefficient of the paste with fly ash at a 20% and 40% replacement level. The results show that the diffusion coefficient can be correctly predicted for 86% of the mixtures for 20% fly ash replacement and 95% of the mixtures for 40% fly ash replacement within the variation of the test method. This work provides a deeper understanding of the impacts of fly ash on the properties of concrete and provides a new method to predict the performance of the diffusion coefficient at different hydration times.